Protective properties of vitamin E on hepatic cell injury caused by pregabalin on male rabbits (Biochemical and histopathological study) - Mohammed Mahmood (Basrah Journal of Veterinary Research)
This study aimed to revel the protective properties of vitamin E on liver injury induced by pregbalin (biochemical and histopathological study) in rabbits. Twenty-four local male rabbits were used in this experimental study under suitable condition of feed and temperature. Rabbits classified into three group: each group 8 rabbits. Group one (control group) received distal water orally daily for 14 days, Group two (pregbalin group) received orally pregbalin 3mg/kg dissolved in normal saline daily for 14 days, Third group received vitamin E (α-tocopherol) 800 IU orally followed in 3 hours by 3 mg/kg of pregbalin dissolved in normal saline daily for 14 days. The biochemical results showed no significant differences in control group, the ALP, GPT and GOT showed significant increase in second pregbalin group. The third group showed significant decrease in ALP and GOT but the GPT showed slightly increase above normal value in control group. The histopathological results showed normal liver histology in control group, second pregbalin group showed infiltration of inflammatory cells specially leukocytes, dilation of blood sinusoids, portal area and central vein in addition to presence of activated kupffer cells. Third group received vitamin E followed by pregbalin showed relatively normal tissue appearance of liver including and similar to control group.